Pembelajaran Fikih Era New Normal di MA Nurul Iman Sidodadi Pringsewu Lampung - Masamah Yukita; Waluyo Erry Wahyudi; Jamal Fakhri (IIQ An Nur Yogyakarta, 2022)
This research aimed to determine the process of learning fiqh in the new normal era at MA Nurul Iman Sidodadi Pringsewu. In the new normal era, the learning process was carried out face-to-face limited in accordance with the policies of the Ministry of Education and Culture (Kemendikbud). This type of research was descriptive qualitative. The data collection technique used the method of observation, interviews, and documentation. Data analysis techniques used data reduction, display data, and conclusions. Meanwhile, checking the validity of the data using source triangulation. The subjects of this research were students of class X in learning fiqh at MA Nurul Iman Sidodadi Pringsewu. The results showed that in the process of learning fiqh the new normal era at MA Nurul Iman had not gone well. Less than optimal learning planning was good in compiling lesson plans using one sheet with limited time for teaching and learning activities. Implementation of teaching and learning activities which include three activity components, namely the beginning, core, and closing. Evaluation of learning in terms of planning was done by determining goals through questions, while analysis of questions was not carried out. Implementation of evaluation in the form of pre-test and post-test to determine the level of student understanding of the learning material.